The Development of the Poaceae Family Scientific Book in the Tabanio Beach Forest on Students' Creative Thinking Ability - Nurul Hikmah; Dharmono Dharmono; Atiek Winarti (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The evaluation of students' creative thinking has not been optimal, the use of books in the Higher Plant Botany course at the Biology Education Faculty of ULM in the Poaceae family sub-material based on creative thinking is still limited, so enrichment teaching materials are needed by utilizing local potential and using aspects of thinking creative. The scientific book development model adapted Tessmer's formative evaluation which was limited to self-evaluation, expert review of 3 ULM Master of Biology Education lecturers which included material experts, linguists and media experts, one-to-one evaluation and small group evaluation which included 8 undergraduate students of Biology Education FKIP ULM who have passed the Higher Plant Botany course. The assessment given by experts to scientific books obtained valid criteria (3.59). Respondents' assessment of the practicality of the content obtained very good criteria (88.89%). Respondents' assessment of the practicality of expectations obtained very good criteria (83%). The observer's assessment on the fulfillment of expectations obtained very good criteria (82%). Assessment of the effectiveness of expectations obtained high criteria (80.80) and increased creative thinking skills at three meetings obtained moderate N-gain criteria. Scientific books are declared valid, practical and effective.Abstrak Belum optimalnya evaluasi berpikir kreatif mahasiswa, penggunaan buku pada mata kuliah Botani Tumbuhan Tinggi di S1 Pendidikan Biologi FKIP ULM pada sub-materi Famili Poaceae berbasis berpikir kreatif yang masih terbatas, sehingga diperlukan bahan ajar pengayaan dengan memanfaatkan potensi lokal dan menggunakan aspek-aspek berpikir kreatif. Model pengembangan buku ilmiah mengadaptasi evaluasi formatif Tessmer yang dibatasi hanya pada self evaluation, expert review dari 3 dosen Magister Pendidikan Biologi ULM yang meliputi ahli materi, ahli bahasa dan ahli media, one-to-one evaluation dan small group evaluation yang meliputi 8 mahasiswa S1 Pendidikan Biologi FKIP ULM yang telah lulus mata kuliah Botani Tumbuhan Tinggi. Penilaian yang diberikan ahli terhadap buku ilmiah memperoleh kriteria valid (3,59). Penilaian responden pada kepraktisan isi memperoleh kriteria yang sangat baik (88,89%). Penilaian responden pada kepraktisan harapan memperoleh kriteria sangat baik (83%). Penilaian observer pada keterlaksanaan harapan memperoleh kriteria sangat baik (82%). Penilaian keefektifan harapan memperoleh kriteria tinggi (80,80) serta peningkatan kemampuan berpikir kreatif pada tiga pertemuan memperoleh kriteria N-gain sedang. Buku ilmiah dinyatakan valid, praktis dan efektif.